Aspectos teórico-metodológicos da produção científica em controladoria governamental: estudo das teses e dissertações dos programas de pós-graduação em contabilidade e controladoria no Brasil - Gomes, Amanda de Oliveira (2013)
Public Administration enhances the ability of society to exercise their rights by providing access to education and health care, where those resources are provided by the own society financed by taxes. Historically in Brazil public funds have been used by particular interests rather than the collective application. In this context, Internal Control has emerged, intended to expand and systemize the activities of Controllership. As a government position, the Controllership is still a relatively new concept, especially within local (municipal) governments. One way to enhance the depth of knowledge with regards to fiscal responsibility and government oversight is through the development of scientific research and an increase in those programs pertaining to the subject in graduate programs. The main purpose of this research is to analyze the theoretical and methodological aspects of Controllership, including justification of the increase in the number of graduate studies available in Accounting and Government Oversight in Brazil. The research is characterized as qualitative and analytical, and uses bibliographical, documentary and content analysis, by developing a bibliometric study on Governmental Controllership. The breadth of the research includes those theses and dissertations available on websites of relevant graduate study programs in Brazil between the span of 2001-2011, totaling 1,338 separate research entries. Among these, results were narrowed using the Governmental Controllership as a keyword, which resulted in 237. These studies were then briefly analyzed to observe the extent of the relationship to Governmental Controllership in which 74 studies were selected from the sample. According to the results, it was concluded that the research focused on Governmental Controllership and rely fundamentally on internal control, although they are still very expressive and have evolved over the years (2001-2011), although they rely upon a traditional approach, being characterized by Public Administration and Accounting, and whose breadth of research stems from legislative analysis, the main one being the Brazilian Constitution.